Karakteristik Polong Kedelai Varitas Unggul yang Terserang Hama Pengisap Polong (Riptortus linearis) pada Kondisi Cekaman Kekeringan - M. Sarjan; Isman Sab’i (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2014)
The objective of this study is to examine the morphological characteristics of the superior soybean varieties against sucking pod pests in drought stress conditions. The investigations have been carried out in June-August 2012 in the greenhouse of the Faculty of Agriculture, University of Mataram. Experiments have been designed by using completely randomized design with treatment consist of eight soybean varieties namely Anjasmoro, Panderman, Burangrang, Lawit, Argomulyo, Kaba, Tanggamus and Grobogan, with 3 replications. The parameters measured were: 1) Tickeness of pods skin, 2) trichome pods length; 3) trichome density of pods, 4) the attacks intensity; 6) plant resistance. Data analysis of the studies were performed using ANOVA on the significance level of 5 percent. The results showed that seven varieties of soybeas tested were tended to have the same length of pod trichome, and they did not have any strong correlation with attack intensity of pod sucking insect pest. In addition, the thickness of pod skin had a strong correlation with attack intensity, the ticker of pod skin, the lower of attack intensity. On the other hand, the density of pod trichome did not have any strong influence on attack intensity of pod sucking pest of soybean